Comparative analysis on the effects of spiritual intelligence on leadership effectiveness among Japanese and Malaysian managers - Aahad, M. Osman-Gani; Kobayashi, Kiyoshi; Kabir, Sardar Md Humayun (2019)
Spiritual intelligence has recently been identified as an important competency for leadership effectiveness. It plays a vital role for enhancing leadership performance in contemporary organizations. It has been recommended as a required competency particularly for leaders who are increasingly being accused of compromising ethical standards. The impacts of such intelligence need to be studied intensively for better understanding and for identifying its influence on leadership performance. Some researchers have emphasized the need for and significance of spiritual intelligence for leadership effectiveness in the workplace, but very few have empirically investigated the impacts of this competency on effective leadership. This research empirically investigated the effects of spiritual intelligence on corporate business leadership effectiveness between two distinct Asian economies, and conducted a comparative analysis to identify the nature of differences. Primary data was collected from 186 managers and their subordinates working in different corporate offices operating in Malaysia and Japan. Structural equation modeling technique was applied for conducting data analysis and the results showed that Japanese managers’ spiritual intelligence had more significant positive effects on leadership effectiveness than Malaysian managers. The empirical evidence found from this study will contribute to developing new knowledge in the theoretical domains of leadership, management and organizational behavior. The findings will also help in developing new leadership assessment criteria, making relevant organizational policy decisions, in developing corporate Leadership Effectiveness Index, as well as for developing new professional competencies of the modern corporate leaders. Implications for future research and professional practice are discussed at the end of this paper.